Opposing Trends of Religious Attendance and Religiosity in Predicting Elders' Functional Recovery after an Acute Myocardial Infarction - Martin, Kathryn Remmes (Journal of religion and health, 2006)
This study examined the role of religion and spirituality in older adults' functional recovery following an AMI. Participants were interviewed within 2 weeks of the AMI about their religious beliefs. Functional recovery was evaluated using the Short Physical Performance Battery (SPPB) at one month and seven months. We found that those who reported attending religious services more frequently had better functional recovery. In contrast, those who considered themselves more spiritual had worse functional recovery. These findings remained after controlling for age, gender, co-morbidity (Charlson Co-Morbidity Scale), depression (CES-D), social support (MOS Social Support Survey), and grip strength in Linear Mixed Models. The implications of the findings are discussed.